Aptamer-Based Colorimetric Probe for trans-Zeatin Detection Using Unmodified Gold Nanoparticle. (27th October 2020) - Sun, Ping; Zhang, Xiwei; Wang, Xianxiang
Abstract : Trans -Zeatin is the major active phytohormone in immature corn kernels. Herein, a highly sensitive, good selective and simple aptamer-based colorimetric method for the detection of trans -zeatin was constructed. The selected aptamer sequence binds with trans -zeatin and induces a duplex-to-aptamer structure switching. The gold nanoparticles (AuNPs) solution is stable with high-concentration salt, which is protected by red complementary DNA. In the absence of trans -zeatin, the color of AuNPs changed from red to blue because aptamer DNA and complementary DNA form double-stranded DNA. Thus, the ratio of absorbance intensities (A522/A650) of AuNPs is changed with the concentration of trans -zeatin. The color change could be observed by the naked eye. The linear range of this method covers a large variation of trans -zeatin concentration from 0.05 to 0.75  μ M. The detection limit is 0.037  μ M. Moreover, this method was applied successfully to detect trans -zeatin in real plant samples.